Analisis Pemberian Informasi dan Sosialisasi serta Ukuran Usaha terhadap Pemahaman UMKM Atas Sak Etap di Kota Batam - Dian Efri Yenty; Rio Rahmat Yusran (JURNAL PUNDI, 2019)
The phenomenon that exists in preparing financial statements of MSMEs is still experiencing problems. Small and medium enterprises think that it is quite difficult and need to be given training or assistance in preparing financial reports in accordance with the standards. The development of MSMEs in Indonesia is still faced with a variety of problems, causing weak competitiveness of imported products, problems, global crisis, low education, lack of accounting skills, perception that accounting is not important in business, the perception that accounting is too complicated to do there is no separation of personal funds and funds used in business processes. This research is expected that small and medium enterprises understand the preparation of financial reports in accordance with financial accounting standards. The sample in this study was 93 MSME respondents at the Cooperative and UMKM Office. This research method uses multiple linear regression analysis. The results of his research stating the provision of information and socialization as well as the size of the business had a positive and significant effect on the understanding of SAK-ETAP in the city of Batam.